2005
DOI: 10.1038/sj.emboj.7600811
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mode recognition of noncanonical tRNAsSer by seryl-tRNA synthetase in mammalian mitochondria

Abstract: The secondary structures of metazoan mitochondrial (mt) tRNAs Ser deviate markedly from the paradigm of the canonical cloverleaf structure; particularly, tRNA Ser GCU corresponding to the AGY codon (Y ¼ U and C) is highly truncated and intrinsically missing the entire dihydrouridine arm. None of the mt serine isoacceptors possesses the elongated variable arm, which is the universal landmark for recognition by seryl-tRNA synthetase (SerRS). Here, we report the crystal structure of mammalian mt SerRS from Bos ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 46 publications
9
108
0
Order By: Relevance
“…On the other hand, although the coiled-coiled N-terminal domain exists in the metazoan mitochondrial SerRS, it does not bind the tRNA extra arm, because its cognate tRNA structures markedly deviate from the canonical cloverleaf secondary structure with highly truncated and/or intrinsically missing arms (40). Consequently, biochemical (41) and recent structural studies (19) have revealed a truly distinctive mode of tRNA binding by mammalian mitochondrial SerRS. The SerRSs from methanogenic archaea also differ markedly from their bacterial-type counterparts, most notably through the absence of the N-terminal coiled-coil (21).…”
Section: Idiosyncratic N-terminal Domains Of Serrs Enzymes Provide Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although the coiled-coiled N-terminal domain exists in the metazoan mitochondrial SerRS, it does not bind the tRNA extra arm, because its cognate tRNA structures markedly deviate from the canonical cloverleaf secondary structure with highly truncated and/or intrinsically missing arms (40). Consequently, biochemical (41) and recent structural studies (19) have revealed a truly distinctive mode of tRNA binding by mammalian mitochondrial SerRS. The SerRSs from methanogenic archaea also differ markedly from their bacterial-type counterparts, most notably through the absence of the N-terminal coiled-coil (21).…”
Section: Idiosyncratic N-terminal Domains Of Serrs Enzymes Provide Trnamentioning
confidence: 99%
“…18), with exception of the mammalian mitochondrial enzyme (19 or domains of life) and bacterial tRNA Tyr species (20). In bacterial-type SerRS, the N-terminal domain forms an antiparallel ␣-helical coiled-coil structure (3,16), whereas in the methanogenic-type counterpart it is significantly larger and composed of a six-stranded antiparallel ␤-sheet capped by a bundle of three helices (H1, H2, and H4) with up-down topology and an additional short helix (H3) that runs almost perpendicular to helix H4 (21) (see Fig.…”
mentioning
confidence: 99%
“…The manner of the Ser-SA interaction by P. horikoshii SerRS is the same as that by T. thermophilus SerRS and Bos taurus mitochondrial SerRS, 27,37 except for the involvement of Ser411 with Ser-SA in the former (Figs. 1C and 2).…”
Section: Introductionmentioning
confidence: 71%
“…The transfer of activated amino acids to different thiols was confirmed by TLC analysis of the reaction mixtures containing 14 C-amino acids (Figure 2). Examination of TLC plates revealed that radiolabeled amino acids were converted into the new products in the presence of the enzymes and various thiols.…”
Section: Thiol Aminoacylation By Aa:cp Ligasesmentioning
confidence: 91%
“…10,11 All seryl-tRNA synthetases (SerRSs) are functional homodimers with a C-terminal active site domain typical for class II aaRSs and an Nterminal domain that is responsible for tRNA binding. [12][13][14][15] We have recently shown that methanogenictype SerRSs display several idiosyncratic structural features and exhibit a different mode of substrate recognition in comparison with bacterial-type SerRSs. [15][16][17] Full-length or truncated SerRS-like proteins, homologous to both types of housekeeping SerRSs have been identified.…”
Section: Introductionmentioning
confidence: 99%